Orofacial findings and serial extraction procedure in Noonan syndrome - Potrubacz Maciej Iancu; Chimenti Claudio; Marchione Laura; Tepedino Michele (Sciendo, 2017)
The case of an 8-year-old female affected by Noonan syndrome is presented. The orofacial findings comprised a skeletal Class III malocclusion, transverse maxillary deficiency, a long face and severe tooth size-arch length discrepancy. The interceptive orthodontic approach focused on addressing the patient's problems while keeping treatment as simple as possible. Management consisted of rapid maxillary expansion and serial extractions in the mandible. Treatment alternatives and results are discussed and a one-year follow-up is provided.